2017
DOI: 10.1371/journal.pone.0183884
|View full text |Cite
|
Sign up to set email alerts
|

The more total cognitive load is reduced by cues, the better retention and transfer of multimedia learning: A meta-analysis and two meta-regression analyses

Abstract: Cueing facilitates retention and transfer of multimedia learning. From the perspective of cognitive load theory (CLT), cueing has a positive effect on learning outcomes because of the reduction in total cognitive load and avoidance of cognitive overload. However, this has not been systematically evaluated. Moreover, what remains ambiguous is the direct relationship between the cue-related cognitive load and learning outcomes. A meta-analysis and two subsequent meta-regression analyses were conducted to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 62 publications
2
30
0
1
Order By: Relevance
“…It has been suggested that the built-in markers on AR images provide visual cues to trigger the display of virtual information. These cues are not intended to provide new information, but to give attentional guidance that encourages the user to take action, thereby reducing cognitive overload [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the built-in markers on AR images provide visual cues to trigger the display of virtual information. These cues are not intended to provide new information, but to give attentional guidance that encourages the user to take action, thereby reducing cognitive overload [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even so, the aim was to stimulate debate within the development team about each step. There might not be an optimal educational strategy for each scenario, but the use of cognitive load theory and multimedia learning theory seems useful in daily practice [27,35,36]. We believe that the benefit of these models is not only in the sound theory behind them, but also that they are specific enough to provide easy-to-follow instructional principles.…”
Section: Discussionmentioning
confidence: 99%
“…Four recent meta-analyses (Alpizar et al, 2020 ; Richter et al, 2016 ; Schneider et al, 2018 ; Xie et al, 2017 ) reported significant small to large effect sizes (Kraft, 2020 ), for both retention and transfer scores, indicating that instructional multimedia with signals was more effective than the formats without signaling features. In addition to these effects with multimedia materials, the positive effects of signaling have also been observed with text-only passages, as described below.…”
Section: Problem: Materials Does Not Emphasize Essential Informationmentioning
confidence: 99%